Pengaruh Pola Asuh Ibu Terhadap Status Gizi Anak Balita di Wilayah Kerja Puskesmas Oepoi Kota Kupang. - Nakmofa, Christine Sarlota Iriani; Anna H. Talahatu, Stefanus P. Manongga (Universitas Nusa Cendana, 2023)
Mothers' parenting style has a significant impact on the nutritional status of young children under five. Numerous mothers indicate unhealthy food parenting behaviors toward their toddlers, which may have an impact on their nutritional intake. Other mothers indicate poor personal hygiene parenting behaviors, particularly in relation to PHBS habit. Taking children to Posyandu may have an impact on monitoring the young children's development and growth. The purpose of this study is to determine whether maternal parenting has an impact on the nutritional status of the young children. This type of research is analytic with cross sectional. A total of 102 samples were selected by purposive sampling. The research was conducted in January-February 2022. Univariate and bivariate data analysis was carried out using the logistic regression test. The test results showed that there was an effect of parenting style 0.000 <0.005 with a 43.0% and risk of 10.105. There is an effect of feeding practices 0.001 <0.005 with a large influence of 36.9% and risk of 5.824. There is an influence of personal hygiene practices. 0.000 < 0.005 with a large influence of 16.5% and risk of 9.462. There is an influence of health care practices 0.000 <0.005 with a large influence of 26.6% and risk of 5.824. Mothers are expected to be able to provide the right food for children in accordance with the nutritional needs of children at the age of five, increase PHBS and always bring children to the posyandu.